2020
DOI: 10.1016/j.clnu.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Link between gut microbiota and health outcomes in inulin -treated obese patients: Lessons from the Food4Gut multicenter randomized placebo-controlled trial

Abstract: Conclusions: Inulin-enriched diet is able to promote weight loss in obese patients, the treatment efficiency being related to gut microbiota characteristics. This treatment is more efficacious in patients who did not receive metformin as anti-diabetic drugs prior the intervention, supporting that both drug treatment and microbiota might be taken into account in personalized nutrition interventions. Registered under ClinicalTrials.gov Identifier no NCT03852069.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 39 publications
5
78
0
Order By: Relevance
“…In our study, we have evaluated the feasibility of both CAP and LSM measurement using transient elastography (TE) (with M or XL probes) to analyze the spectrum of MAFLD severity (i.e. steatosis and fibrosis degree) in obese individuals recruited prospectively in St Luc Hospital (Belgium) in the Food4Gut study 20 . This allowed us to elaborate the link between MAFLD severity and extra-hepatic alterations incriminating adiposity, skeletal muscle dysfunction and the gut microbiome.…”
Section: Smdimentioning
confidence: 99%
“…In our study, we have evaluated the feasibility of both CAP and LSM measurement using transient elastography (TE) (with M or XL probes) to analyze the spectrum of MAFLD severity (i.e. steatosis and fibrosis degree) in obese individuals recruited prospectively in St Luc Hospital (Belgium) in the Food4Gut study 20 . This allowed us to elaborate the link between MAFLD severity and extra-hepatic alterations incriminating adiposity, skeletal muscle dysfunction and the gut microbiome.…”
Section: Smdimentioning
confidence: 99%
“…110 Similarly, inulin-enriched diet is able to promote weight loss in obese patients and its effect is related to the characteristics of intestinal flora. 111 Several studies have also found the role of prebiotics in lowering blood pressure, 92 preventing low-density lipoprotein oxidation, 112 and improving visceral obesity. 113 Although the current scientific evidence does not support the use of prebiotics to treat HF patients or reduce plasma TMAO levels, it can still be used in further trials for CVD.…”
Section: Tang Et Al (2013) 133mentioning
confidence: 99%
“…43 Like in mice, the increase in genus Akkermansia caused by metformin was also found in rats treated with HFD and diabetic rats. 41,45 We found ten studies on the effect of metformin on the gut microbiota in obese or T2DM patients, two of which were conducted in obese patients 50,51 and eight in T2DM patients [52][53][54][55][56][57][58][59] (Table 3) compared the changes in the gut microbiota of newly diagnosed T2DM patients (without drug treatment before the visit) who received metformin for different follow-up times (from 3 days to 2 years). Four studies were conducted in T2DM patients who had received drug treatment and compared the gut microbiota of patients with vs without metformin treatment.…”
Section: Metformin and The Gut Microbiotamentioning
confidence: 99%
“…53 Two studies on obese patients also found that metformin significantly increased the proportion of the Escherichia/Shigella group. 50,51 Dysbiosis in gut microbiota is strongly associated with the pathogenesis of obesity and T2DM. The composition of gut microbiota exhibited significant differences among obese, T2DM and healthy individuals.…”
Section: Metformin and The Gut Microbiotamentioning
confidence: 99%